Sistem Penjaminan Mutu Pendidikan Tinggi di Indonesia - Rifa'i, Andi Arif (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2019)
Quality assurance is an important part of the higher education system which ensures that the effort to achieve quality is in accordance with the quality standards set by the government. The problem of the low quality of human resources of a nation is a manifestation of the inability of the quality assurance system to work effectively. Application of a model that is less effective in quality assurance, will have an impact on achieving the quality of Education. In Indonesia, various changes in the regulation of the quality assurance system began in 2006 - until now, basically both conceptually but not optimally in implementation. Internal and external quality assurance of higher education (HE) institutions has not produced satisfactory results, with the still low competitiveness of HE graduates and the competitiveness of the nation's human resources.